Bone Marrow and Karyotype Findings of Patients with Pancytopenia in Southern Iran - Safaei, Akbar (Shiraz University of Medical Sciences, 2014)
Background: Pancytopenia is a manifestation of a wide range of disorders. The main prognostic factor for predicting outcome and response to treatment is based on the underlying cause. To detect the root cause of this problem, depending on other accompanied signs or symptoms, the need for bone marrow examination and other advanced work ups is different at least at the practical level. This study focuses on the karyotype abnormality and to demonstrate the ability of this complimentary study in diagnosis and prognosis of such patients. Methods: In this cross sectional study, bone marrow aspiration samples of all patients with Pancytopenia underwent cytogenetic investigation on bone marrow aspiration. Gathered data were analyzed by SPSS software.  Results: Among the 100 eligible patients, 67% revealed hypercellular, 19% had hypocellular and 13% had normocellular marrow. Most common causes of pancytopenia were myelodysplastic syndrome (MDS) (33%), MDS vs. megaloblastic anemia (23%) and acute leukemia (18%). Thirty one patients had karyotype abnormality in which majority (13 patients) were diagnosed as MDS followed by 11 patients with acute leukemia. Conclusion: Beside bone marrow examination, there is a need for more supplementary studies like karyotyping to detect the exact cause of pancytopenia. It is concluded that cytogenetic study on bone marrow aspiration can be a complementary test in diagnosis of pancytopenic patients. However, there are also cases where diagnosis even with implementing bone marrow examination and cytogenetic analysis is not possible. Such patients require more clinical follow-up and investigation.